Case studies in Islamic banking and finance : case questions & answers - Kettell, Brian (Chicester, East Sussex : Wiley, 2011)
ICase Studies in Islamic Banking and Finance/i is a pioneering resource that provides practical insights into the real world of Islamic financial transactions, and illustrates the complexities of this rapidly growing mode of modern finance./ Based around 12 individual cases, the book stimulates discussion and develops the reader's understanding of Islamic finance by contrasting the theoretical concepts discussed in the author's companion text Introduction to Islamic Banking and Finance with practical real world situations. The cases cover core Islamic banking and finance topics including the Ijara, Mudaraba and Musharaka contracts; Islamic mortgages for home finance; leverage; and issues involved in opening an Islamic bank. Financial statement analysis for Islamic banks, the implications for fund management for equity investing and the impact of loan defaults on Islamic and conventional banks are also included. Each chapter concludes with a set of questions designed to test the reader's understanding of each case, with suggested solutions at the end of the book./ This book is a must have resource for those wishing to apply their understanding of this complex subject and is an essential read for anyone seeking practical examples of how to apply the concepts in a real world environment.
Front Matter -- Case Study 1: Ijara Contract -- Case Study 2: Musharaka Contract -- Case Study 3: Diminishing Musharaka Contract -- Case Study 4: Mudaraba Contract -- Case Study 5: Murabaha, Musharaka, Ijara and Ijara wa Iqtina Contracts -- Case Study 6: Islamic Home Finance -- Case Study 7: Sources of Finance for Islamic Banks -- Case Study 8: Financial Statement Analysis for Islamic Banks -- Case Study 9: Islamic Investment Prohibitions -- Case Study 10: Opening an Islamic Bank within aWestern Regulatory Framework -- Case Study 11: Leverage and Islamic Banking -- Case Study 12: Impact of Non-performing Loans on Islamic and Conventional Banks -- Case Study Answers -- Glossary -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Banks and banking -- Islamic countries; Finance; Banking law (Islamic law) -- Case studies; Banks and banking -- Religious aspects -- Islam -- Case studies; Banks and banking; Finance -- Religious aspects -- Islam -- Case studies; SOCIAL SCIENCE -- Essays; SOCIAL SCIENCE -- Reference; Banks and banking; Finance; Islamic countries; Electronic books; Electronic books